Рослинний покрив ботаніко-географічної ділянки “Кавказ” Національного ботанічного саду ім. М.М. Гришка НАН України. Повідомлення 1. Видове різноманіття - Shynder, O.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Information on the species diversity of living plants collections in phyto-geographical plot “Caucasus” in the M.M. Gryshko National Botanical Garden of the NAS of Uk raine are given. The fund of living plants in this plot includes 406 species from 89 families. Synopsis of 350 species of native flora of the Caucasus is shown. 216 species of plants directly from the Caucasus to the botanical gardens are relocated. Sistematical, biomorphological and ecotope structures of the collection of plants are analyzed. The largest number of plant species in plot “Caucasus” is forest (174 species). Meadow species – 78. The total number of plant species in the plot is the largest among phyto-geographical plots of Botanical garden. In the future collection of living plants in plot “Caucasus” expedient to increase by 35–60 woody and 100–120 herbaceous species.